2014
DOI: 10.1016/j.aat.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of ropivacaine 0.5% versus ropivacaine 0.2% for transabdominis plane block in providing postoperative analgesia after appendectomy

Abstract: The effectiveness of two different concentrations of ropivacaine (0.5% versus 0.2%) given via TAP block was comparable in providing postoperative analgesia for patients undergoing appendectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…With a vasoconstrictive effect at low concentration (0.063-0.5%) 34 , ropivacaine is often not used with epinephrine 7 which also has an unpredictable role in the cardiovascular system. The concentrations of ropivacaine in this study were chosen to be 0.2%, 0.33%, 0.5% based on the findings that scalp infiltration by 0.5% ropivacaine reduced postoperative pain received craniotomy in previous study 17 and 0.2%, 0.33% ropivacaine are usually preferred for peripheral nerve block procedures [35][36][37] . In our study, pre-incision SNB with 0.2% and 0.33% ropivacaine decreased the postoperative pain for up to 2 hours, and 0.5% ropivacaine used as postoperative analgesia had longer duration for up to 4 hours after craniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…With a vasoconstrictive effect at low concentration (0.063-0.5%) 34 , ropivacaine is often not used with epinephrine 7 which also has an unpredictable role in the cardiovascular system. The concentrations of ropivacaine in this study were chosen to be 0.2%, 0.33%, 0.5% based on the findings that scalp infiltration by 0.5% ropivacaine reduced postoperative pain received craniotomy in previous study 17 and 0.2%, 0.33% ropivacaine are usually preferred for peripheral nerve block procedures [35][36][37] . In our study, pre-incision SNB with 0.2% and 0.33% ropivacaine decreased the postoperative pain for up to 2 hours, and 0.5% ropivacaine used as postoperative analgesia had longer duration for up to 4 hours after craniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Though we preferred to use intravenous paracetamol as sole rescue analgesic in the present study as compared to opioid analgesics, the overall cumulative analgesic consumption with either of the local anesthetic in both the groups was less and comparable to studies that have used opioids for postoperative analgesia by the use of these local anesthetics in other peripheral blocks. [ 16 24 25 ] In addition, by using paracetamol as rescue analgesic, the unwarranted side effects of opioids were also avoided. The rescue analgesic was administered only if VAS exceeded 40.…”
Section: Discussionmentioning
confidence: 99%
“…Recently positive results have been published regarding the pre-emptive incision site infiltration with a local anaesthetic. Studies demonstrated that this decreases the total opioid consumption and lowers pain score experienced by patients in the first 24 h after surgery [182184]. …”
Section: Post-operative Carementioning
confidence: 99%